PENGARUH POLA TIDUR TERHADAP MOTIVASI BELAJAR SISWA - Nidar Yusuf; Titi Rohmah (Universitas Sarjanawiyata Tamansiswa, 2019)
This research is motivated by the existence of patterns or sleep schedules of students who are less organized so that it can interfere with their concentration in learning, besides that physical health can also decrease. Because sleep is a repetitive state, if people get enough sleep, they feel their energy has recovered. This shows sleep provides time for repair and healing of the body's systems. The purpose of this study was to determine the effect of sleep patterns on student learning motivation. The approach used in this study is quantitative with survey research methods and with regression analysis techniques, with the hypothesis that there is no effect of sleep patterns on student motivation. The results showed that there was no significant effect on sleep patterns on student motivation in school. In the research results, the value of the regression direction coefficient is 0.047 and the constant value is 34.631. Also produced count = 0.584 with a significant value of 0.562> 0.05. While the 2.011 table value can be interpreted that 0.584 <2.011 then Ho is accepted and Ha is rejected it can be concluded that there is no significant effect between the independent variable (x) and the dependent variable (y).